Structured collaboration across a transformative knowledge network-learning across disciplines, cultures and contexts? - Ely, Adrian (2020)
Realising the Sustainable Development Goals (SDGs) will require transformative changes at micro, meso and macro levels and across diverse geographies. Collaborative, transdisciplinary research has a role to play in documenting, understanding and contributing to such transformations. Previous work has investigated the role of this research in Europe and North America, however the dynamics of transdisciplinary research on 'transformations to sustainability' in other parts of the world are less well-understood. This paper reports on an international project that involved transdisciplinary research in six didierent hubs across the globe and was strategically designed to enable mutual learning and exchange. It draws on surveys, reports and research outputs to analyse the processes of transdisciplinary collaboration for sustainability that took place between 2015-2019. The paper illustrates how the project was structured in order to enable learning across disciplines, cultures and contexts and describes how it also provided for the negotiation of epistemological frameworks and didierent normative commitments between members across the network. To this end, it discusses lessons regarding the use of theoretical and methodological anchors, multi-loop learning and evaluating emergent change (including the didiiculties encountered). It odiers insights for the design and implementation of future international transdisciplinary collaborations that address locally-specific sustainability challenges within the universal framework of the 2030 Agenda for Sustainable Development.